Nanovaccine targeting in colorectal cancer: a multi-dataset analysis of CEA expression, cytokine profiles, and co-expressed genes - Zdrehus, Razvan-Septimiu; Mitrea, Cristina; Mocan, Lucian (Medicine and Pharmacy Reports, 2025)
Background. Carcinoembryonic antigen (CEA/CEACAM5) is a well-established tumor-associated antigen overexpressed in epithelial malignancies, including colorectal cancer (CRC). While its diagnostic and therapeutic relevance is recognized, its immunological context and potential as a nanovaccine target remain underexplored. Aim. This study aims to enable the rational design and refinement of CEA-based nanovaccines by integrating transcriptomic and spatial data to identify immunologically relevant co-expressed biomarkers and potential therapeutic targets. Methods. We conducted an integrative bioinformatics analysis using transcriptomic data from TCGA-COAD, GEO, and spatial datasets (GSE207843, GSE226997), complemented by differential gene expression analysis (GSE245218). CEACAM5 expression was correlated with cytokine profiles (IL10, IFNG, TNF, IL1B, IL12A, IL4), immune cell infiltration (via xCell), and co-expression networks. Genes with Spearman ρ > 0.75 were prioritized as vaccine candidates and evaluated through oncofetal expression and literature curation. Results. CEACAM5 expression was inversely correlated with IFNG, IL10, TNF, and IL1B, suggesting a potential immunosuppressive phenotype. xCell analysis revealed negative trends between CEACAM5 and effector immune populations including CD8⁺ T cells and NK cells. Spatial transcriptomics confirmed CEACAM5 compartmentalization in tumor epithelium with minimal cytokine overlap. Co-expression analysis identified EPCAM and ATP10B as high-confidence candidates. Embryonic vs. adult differential analysis (GSE245218) confirmed their oncofetal expression patterns. Gene ontology analysis revealed downregulation of antibacterial humoral immune pathways. Conclusion. CEACAM5 defines a distinct immune-silent tumor phenotype and co-localizes with other vaccine-relevant genes such as EPCAM. This study provides a comprehensive immunogenomic rationale for CEACAM5-directed nanovaccine development and proposes EPCAM and ATP10B as co-targets based on tumor-specific and developmental expression profiles.